The Experiences Of Infection And Prevention Control Nurses (Ipcns) In Cultivating Hand Hygiene - Erna Tsalatsatul Fitriyah; Meidiana Dwidiyanti; Luky Dwiantoro (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2018)
Healthcare-Associated Infections (HAIs) are infections that patients get while undergoing treatment and medical procedures in the hospital or other healthcare facilities after more than 48 hours. Improving the quality of hand hygiene practices can reduce pathogen transmission that causes HAIs. Infection and Prevention Control Nurses (IPCNs) as the pioneers of infection prevention and control should play an active role in cultivating hand hygiene in the hospital environment. Unfortunately, until the present time, there is evidence that IPCNs have not played their roles optimally in making hand hygiene a culture in the hospital. This study aimed to explore the experiences of IPCNs in cultivating hand hygiene at the inpatient wards in a regional hospital in Semarang, Indonesia. This study used a qualitative research design with a phenomenological approach. The samples were recruited using purposive sampling technique, consisting of three IPCNs as the main participants, and one Infection Prevention and Control Officer (IPCO) and three Infection Prevention and Control Link Nurses (IPCLNs) as the triangulation participants. Data were collected using semi-structured in-depth interviews and analyzed using the content analysis. The results revealed two themes. First, the appropriate education implementation and its documentation are important to provide an adequate understanding of medical and non-medical staffs, patients and families so that they are willing to perform hand hygiene properly. Second, the implementation of hand hygiene requires complete infrastructures and facilities, proper monitoring and evaluation system, as well as appropriate role models and motivation so that hand hygiene can become a positive culture. This study concludes that IPCNs have positive and negative experiences while trying to cultivate hand hygiene. IPCNs understand and agree that their ability to provide proper education and sensitivity to the factors affecting the implementation of hand hygiene can improve the people’s understanding and compliance with hand hygiene. In the end, hand hygiene will eventually become one of the positive cultures in the hospitals. Keywords: IPCNs, hand hygiene